The chromatin‐remodelling factor PICKLE interacts with CONSTANS to promote flowering in Arabidopsis. (30th April 2019) - Jing, Yanjun; Guo, Qiang; Zha, Ping; Lin, Rongcheng
Abstract: In many flowering plants, successful reproductive development depends on the plant's ability to sense seasonal photoperiodic changes and adjust its vegetative growth accordingly. In Arabidopsis thaliana, the day‐length‐dependent accumulation of CONSTANS (CO) is crucial for the rhythmic activation of FLOWERING LOCUS T ( FT ) expression at dusk under long days. However, the regulation of photoperiod‐dependent changes of the diurnal FT expression pattern at the chromatin level is largely unknown. In this study, we show that the ATPase‐dependent chromatin‐remodelling factor PICKLE (PKL) acts through the CO‐FT regulatory module and contributes to FT activation in leaf vasculature. PKL physically interacts with CO, and this interaction facilitates their binding to the common regions of FT chromatin in response to photoperiod. Long‐day signal triggers the FT chromatin switch between the active state at dusk and the inactive state at night, and PKL is responsible for the diurnal state switch. Thus, our study reveals that PKL activates FT transcription likely through facilitating access of CO to FT chromatin at dusk to synchronize flowering time in response to environmental cues. Abstract : FLOWERING LOCUS T ( FT ) expression is rhythmically regulated in response to the photoperiod cue to ensure proper flowering, yet it remains unknown how photoperiod‐dependent FT chromatin state switch is achieved. Here, we show that long‐day signal triggers the FT chromatin switch between the active state at dusk and the inactive state at night, and PICKLE (PKL) is responsible for the diurnal state switch. PKL physically interacts with CONSTANS (CO), and this interaction facilitates their binding to the FT chromatin in response to photoperiod. Hence, PKL and CO act synergistically to activate FT expression.